EVOLUTION OF GENRE PREFERENCES IN THE WORK OF DMITRY REVYAKIN (Multidisciplinary Journal of Science and Technology, 2026)
The article examines the evolution of genre preferences in the creative work of Dmitry Revyakin — a poet, composer, and the leader of the band Kalinov Most. The study analyzes the main stages of the artist’s development: from an early rock–folk synthesis to philosophical, mystical, and religious forms. Special attention is given to the interaction of genre models (folk rock, singer-songwriter tradition, spiritual poetry) and the individual authorial style.